Research at the IMF : Relevance and Utilization. - International Monetary Fund. Independent Evaluation Office (Washington, D.C. : International Monetary Fund, 2013)
This evaluation report assesses research produced at the IMF between 1999 and 2008, focusing on the relevance and utilization of research to member country authorities, IMF staff, and other stakeholders. The report also examines the technical quality and management of research and offers recommendations for enhancing the relevance of research, improving the technical quality of analytical work, promoting openness to alternative perspectives, and improving the management of research.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet